Blood profile and productive performance after partial substitution of maize grain with ancient wheat lines by-products in organic laying hens' diet. (December 2020) - Lombardi, Pietro; Addeo, Nicola F.; Panettieri, Valentina; Musco, Nadia; Piccolo, Giovanni; Vassalotti, Giuseppe; Nizza, Antonino; Moniello, Giuseppe; Bovera, Fulvia
Abstract: The aim of this research was to evaluate the effects of the partial substitution of maize grain with local ancient wheats by-products in an organic laying hens farm on animal performance and blood profile, as well as on eggs quality. A total of 80 Hy-Line W-36 Single Comb White Leghorn, 18 weeks old hens were homogenously divided into two groups. The two groups (40 laying hens each, 8 replicates, 5 hens/replicate) were fed two isoprotein and isoenergetic diets: the Control group (C) was fed a standard, organic maize-soybean meal diet whereas in the Ancient Grains group (AG) part of the maize grain was replaced by a mix of ancient grains middling, consisting in 50:50 of Triticum aestivum var. spelta (spelt) and Triticum durum dicoccum L. (emmer wheat). The birds fed the maize based-diet (C) showed a higher ( P  < 0.01) egg weight and feed intake than the Ancient Grains (AG) group. By contrary, the feed conversion ratio was more favourable ( P  < 0.05) in hens fed the Ancient Grains diet. The eggs produced by the hens fed the Control diet showed higher length and width than the other group ( P  < 0.01). The shell thickness and strength were also higher in the Control group (P < 0.01 and P  < 0.05, respectively). The experimental dietary treatment positively affected some blood parameters. The Control group showed higher levels of cholesterol and triglycerides ( P  < 0.05) as well as of alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT) ( P  < 0.01). In addition, butyrate, which may have great implications for the regulation of the immune response, resulted significantly higher in the caecal content of hens from the Ancient Grains group. Overall, the Ancient Grains diet seemed to be able to guarantee the production performances with positive effects on the animal health. Highlights: Sustainability of animal productions is an important target. The use of local feed resources can help sustainability and animal help. The ancient wheats can bee used in organic laying hens farm.